On the practice of safety - Manuele, Fred A. (Hoboken, N.J. : John Wiley & Sons, Inc., 2013)
"On the Practice of Safety continues to be an unparalleled resource on best safety practices. It supplies the reader with the core information that everyone who is in the safety field must know. Each chapter is written in a self contained unit that can be used on its own to cover a topic. The new edition updates all of the chapters from the previous edition while adding new material. Topics in these new chapters include sustainability, lean concepts, management of change/pre-job planning, leading and lagging indicators, and indirect and direct accident costs"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Industrial safety; Electronic books